Crystal Palaces, Inner Courtyards and Devotional Trees: Symbolism and Shared Spaces between Iberian Sufis and Carmelite Mystics - Conde Solares, Carlos (Anaquel de Estudios Árabes, 2018)
This study explores the shared spaces between Sufism, Andalusian spirituality and Christian Mysticism in the Iberian Peninsula. This article analyses mystical symbols and devotional constructions in a medieval and Golden Age chronological framework. In doing so, it seeks to establish the dynamics of interaction within a spiritual corpus that ranges from Oriental Sufism to Carmelite Mysticism via Andalusian and Mudejar spiritualities. This collation of myriad materials reveals a common thread and a collective tradition shaped by spiritual dialogue, collaboration and debate within a shared set of devotional coordinates.
Keywords: Sufism; Mysticism; Andalusian spirituality; St John of the Cross; Rūmī